Penanaman Nilai-Nilai Religius dalam Kegiatan Rutinan Hadroh Mashoka (Majelis Sholawat) Putri kecamatan Kuwarasan - Alfi, Khaerum (IAINU Kebumen, 2022)
Religious value is the highest and absolute value, this value comes from human trust and belief. Religious values reflect faith in God Almighty which is manifested in the behavior of carrying out religious teachings and beliefs that they adhere to. Religious values are values regarding the concept of religious or religious life in the form of bonds or relationships that govern humans with their gods. Meanwhile, the cultivation of religious values can be through example, namely by imitating the stories of the Prophet, the birth of the Prophet and the Prophet's Family. Sholawat is a poem of praise and flattery for the Prophet Muhammad SAW. Importantly, in the routine activities of Hadroh MASHOKA Putri in Kuwarasan sub-district, it is a means of learning the development of religious values in addition to preserving religious culture. The results of the study show that the cultivation of religious values through Mashoka Putri hadroh activities has three stages, namely by delivery or giving